2016
DOI: 10.3386/w22877
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Executives Make a Difference? The Impact of Female Leadership on Gender Gaps and Firm Performance

Abstract: We investigate the effects of female executives on gender-specific wage distributions and firm performance. We find that female leadership has a positive impact at the top of the female wage distribution and a negative impact at the bottom. Moreover, the impact of female leadership on firm performance increases with the share of female workers. Our empirical strategy accounts for the endogeneity induced by the non-random assignment of executives to firms by including in the regressions firm fixed effects, by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…However, in line with evidence for advanced economies (Wolfers, 2006) and Latin America (Abrahams et al, 2016;Flabbi et al, 2014), once we controlled for firm characteristics other than industries and countries, we found that the productivity gap vanished for women-led businesses and for firms that were predominantly owned by women (dominant owner). The Tables 6.12-6.14 consistently show that there was a gender gap in productivity irrespective of the measure of gender composition, with the only exception being the dummy female owner, which identifies firms with at least one woman among the owners, and women-led business, which was not significant when firm performance was measured by TFP, even though the coefficient was negative.…”
Section: Is There a Gender Gap In Firm Productivity?supporting
confidence: 61%
See 4 more Smart Citations
“…However, in line with evidence for advanced economies (Wolfers, 2006) and Latin America (Abrahams et al, 2016;Flabbi et al, 2014), once we controlled for firm characteristics other than industries and countries, we found that the productivity gap vanished for women-led businesses and for firms that were predominantly owned by women (dominant owner). The Tables 6.12-6.14 consistently show that there was a gender gap in productivity irrespective of the measure of gender composition, with the only exception being the dummy female owner, which identifies firms with at least one woman among the owners, and women-led business, which was not significant when firm performance was measured by TFP, even though the coefficient was negative.…”
Section: Is There a Gender Gap In Firm Productivity?supporting
confidence: 61%
“…Females are also less likely to be promoted or elected into positions of authority. As reported in Flabbi et al (2014) in 2012, 433 of the top 500 Latin American companies had no women senior executives and only nine had a woman CEO. This was confirmed in a report by ILO (2015) stating that in Jamaica and Saint Lucia the share of women-managers in businesses was higher than men but that women were mainly concentrated in middle management positions and under-represented in the most senior positions.…”
Section: Variable (Abbreviation) Definitionmentioning
confidence: 99%
See 3 more Smart Citations